Idiopathic nephrotic syndrome: the EBV hypothesis - Dossier, Claire; Jamin, Agnès; Deschênes, Georges (Pediatric research, 2017)
Steroid sensitive nephrotic syndrome is marked by a massive proteinuria and loss of podocytes foot processes. The mechanism of the disease remains debated but recent publications suggest a primary role of Epstein-Barr Virus (EBV). EBV replication in the peripheral blood is found in 50% of patients during the first flare of the disease. The genetic locus of steroid sensitive nephrotic syndrome was also identified as influencing antibodies directed against EBNA1. EBV is able to establish, latent benign infection in memory B cells that display phenotypes similar to antigen-selected memory B cells. Consistently, memory B cells reconstitution after rituximab infusion is a predictor of the relapse of proteinuria. We suggest that a specific anti-EBNA1 antibody internalized in the podocytes via the neonatal Fc receptor might cross-react with a major protein present in the same cell trafficking compartment. The diversion of this major podocyte protein in the urinary space and the subsequent depletion is supposed to result in podocyte damages with loss of foot processes and massive proteinuria. Immunosuppression of B cells and subsequent clearance of anti-EBNA1 antibodies would lead to a restoration of the normal level of the protein allowing recovery of proteinuria and of normal podocyte morphology.